Pengaruh Customer Relationship Management dan Kualitas Layanan Terhadap Kepuasan dan Loyalitas Pelanggan Media Advertising di Samarinda - Ade Saputri; Syarifah Hudayah; Zainal Abidin (e-Journal Ekonomi Bisnis dan Akuntansi, 2020)
The purpose of this study was to analyze the effect of customer relationship management and service quality on customer satisfaction and loyalty of advertising media companies in Samarinda. The population in this study were customers of advertising media companies in Samarinda. Using accidental sampling, the sample in this study was 100 respondents. The analysis in this study is path analysis with the SPSS program. The results showed that CRM has a positive and significant effect on customer satisfaction, CRM has a positive and significant effect on customer loyalty, service quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer loyalty in advertising media in Samarinda city.